2021
DOI: 10.3390/cells10040887
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical Properties of Cancer Cells

Abstract: Since the crucial role of the microenvironment has been highlighted, many studies have been focused on the role of biomechanics in cancer cell growth and the invasion of the surrounding environment. Despite the search in recent years for molecular biomarkers to try to classify and stratify cancers, much effort needs to be made to take account of morphological and nanomechanical parameters that could provide supplementary information concerning tissue complexity adaptation during cancer development. The biomech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 126 publications
0
32
0
3
Order By: Relevance
“…AFM-based mechanobiological measurements are now widely performed, in particular for living normal and cancerous cells (see reviews: Krieg et al 2019 ; Runel et al 2021 ). The elasticity (Young’s modulus) of living cells was first quantified to be 0.013–0.15 MPa from the force-versus-indentation curve measurements on a lung carcinoma cell (Weisenhorn et al 1993 ).…”
Section: Top Five List Justificationmentioning
confidence: 99%
“…AFM-based mechanobiological measurements are now widely performed, in particular for living normal and cancerous cells (see reviews: Krieg et al 2019 ; Runel et al 2021 ). The elasticity (Young’s modulus) of living cells was first quantified to be 0.013–0.15 MPa from the force-versus-indentation curve measurements on a lung carcinoma cell (Weisenhorn et al 1993 ).…”
Section: Top Five List Justificationmentioning
confidence: 99%
“…Recent studies have demonstrated effective tools to investigate mostly mechanical properties of glioma cells using fluorescence microscopy [15][16][17][18][19][20][21][22][23][24][25][26][27], 2-photon imaging [11,28], atomic force microscopy [16,29,30], single-cell force spectroscopy [16], and microfluidic technologies [31][32][33][34][35][36][37][38][39]. In contrast to mechanical features, electrical properties of glioma cells have not been extensively interrogated.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, indexing assessment of the metastatic state and its early prediction is fundamental for enlightening cancer progression, improving early cancer prognosis and developing therapeutic schemes 3,4 . Tissue microenvironmental factors, including stiffness and topography (nuclei's shape, morphology, and texture specificity), contribute to the targeting preferences of metastatic cancers [5][6][7][8][9] because biological and mechanical/topographic parameters are associated with cancer cell proliferation, migration and metastasis 7,10,11 . Cancer cells regulate their stiffness to match the ECM local environment by adjusting viability to different structural proteins' complex ECM topographical environment.…”
Section: Introductionmentioning
confidence: 99%
“…Along the above lines, a novel methodology of probing the mechanics of tumours emerged as a supportive method to find the link between the mechanical properties of single tumour cells and their metastatic potential [18][19][20] . However, although several techniques exist, including the atomic force microscopy (AFM) 5,21,22 , to measure the mechanical properties of single cells, information on the mechanics of tumour cells in the ECM is missing because most measurements are made on cultured tumour cells 10,23 . Besides, each method has a particular set of parameters that do not consider patient-to-2 patient variations, which is an additional drawback in comparing different studies 5,24 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation